Childhood Career Development in Mainland China: A Research and Practice Agenda. Issue 3 (September 2014) - Liu, Jianwei; McMahon, Mary; Watson, Mark
<x xml:space="preserve">Abstract</x> Career development in adolescence and adulthood has been widely researched; however, less is known about childhood career development, particularly in non‐Western cultures. This is especially the case in mainland China, where children grow up in a unique context. The Confucian tradition of emphasizing education as an important social ladder and parents' role in their children's development may restrict children's development of career‐planning skills. By contrast, the shift from a planned economy to a market economy enables individuals to choose careers and demands that individuals have career‐planning skills. The elementary school years could be a starting point to develop such skills by providing career guidance for children. This article considers childhood career development in mainland China, discusses the status quo of childhood career development research and practice, and considers an agenda for future research and practice.